Designing Plasmon‐Enhanced Thermochromic Films Using a Vanadium Dioxide Nanoparticle Elastomeric Composite. Issue 4 (23rd December 2015) - Moot, Taylor; Palin, Cass; Mitran, Sorin; Cahoon, James F.; Lopez, Rene
Abstract : Vanadium dioxide (VO2 ) is a common material for use in thermochromic windows due to a semiconductor‐to‐metal transition (SMT) that is coupled with a change in infrared opacity. Commercialization of VO2 ‐based thermochromic technology is hampered by relatively expensive synthesis and film fabrication techniques as well as overall low performance as a window material. Here, simulations that indicate the plasmon resonance of VO2 nanoparticles in a composite film, which can be tuned to achieve record performance values, are reported. These simulations are experimentally verified by fabricating a VO2 nanoparticle composite in an elastomeric matrix using low‐temperature and atmospheric processing conditions. The optical properties of the films are analyzed, yielding visible transmittance and infrared modulation values within the range of top‐performing thermochromic windows. In addition, an improvement in performance is observed upon stretching the films, an effect that can be attributed to a local refractive index modulation. The results highlight the potential use of elastomeric composites as a low‐cost route to higher‐performance smart windows. Abstract : Simulations show potential high performance of colloidal‐based thermochromic windows by tuning vanadium dioxde nanoparticle plasmon resonance. VO2 nanoparticles are synthesized and elastomer films are fabricated to study this experimentally. The optical and elastomer properties at low and high temperatures and the performance metrics are measured. Reasonable performance values are achieved and improved through stretching the elastomer film.